Optimal minimal solution for total losses using evolutionary programming based on reactive power load variation by considering voltage stability index / Nor Shazwani Zulkifli - Zulkifli, Nor Shazwani (2014)
The stability of an electrical system is a very important matter in order to prevent electrical failure and electricity blackout. With the development of country and increasing number of population, there is an increase in the electricity demand. So, there will be a lot of continuous change in the line interconnection, supplier and electricity demand which makes the system more complicated. As a result, the system will be working under stress condition and its operating point will be close to its voltage stability limit. The common consequence from this problem would be a voltage collapse which will increase the total losses in the system. Hence, a reactive power management must be applied to mitigate this problem. Besides, it is also important to determine the voltage limit of the system before it becomes unstable so that the appropriate actions can be taken earlier. This paper presented Evolutionary Programming based optimization technique to find optimal minimal solution for total losses considering reactive power load variation. The research and investigation was carried out on IEEE 30-buses system and the result obtained was analyzed. In order to determine the stability strength of the system after optimization, a voltage stability index is used. The system is considered unstable if the value obtained is equal or larger than 1. If this happens, the system will began to collapse by causing a voltage drop in the corresponding bus. Two types of voltage stability index which is Line Stability Index and Line Stability factor were used in order to compare their reliability in determining the stability of the system.